Keanekaragaman Echinodermata dan Hubungannya dengan Komposisi Lamun pada Zona Intertidal Pantai Kiama, Sulawesi Utara - Julianti Malensang; Revolson A. Mege; Nonny Manampiring (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Seagrass beds are coastal ecosystems that have important ecological functions as a provider of habitat, food sources, protection, and reproductive areas for various marine life including Echinoderms. This study aims to analyze the diversity of Echinoderms and their relationship with seagrass distribution in Kiama Beach, Melonguane District, Talaud Islands Regency. The research was conducted in the intertidal zone at three stations using the exploration method with purposive sampling technique. Each station is divided into three plot installation zones measuring 4 × 4 meters, with observations made at low tide. Environmental parameters (temperature and pH), type and number of Echinoderm individuals, and seagrass species were recorded and analyzed using the Shannon-Wiener diversity index and product moment correlations. The results showed that the Echinoderma community consists of two classes and five species: Archaster typicus, Linckia laevigata, Culcita novagueniae, Holothuroidea scabra, and Holothuroidea forskali, with the Asteroidea class dominating (75%). The diversity index (H') value was relatively low at all stations with a range of 0.6261–0.6631. Seagrass beds consist of five species, namely Halophila ovalis, Cymodocea rotundata, Thalassia hemprichii, Halodule uninervis, and Syringodium isoetifolium, with the highest abundance found in Halophila ovalis. Correlation results showed a strong to very strong relationship between the abundance of Echinoderms and certain seagrass types (r = 0.77–0.99) as well as a strong correlation at the overall level of the station (r = 0.74). This study confirms that the presence and abundance of Echinoderms is greatly influenced by the density and composition of seagrass species. These findings provide important baseline data for the management and conservation of seagrass beds as a support for the sustainability of coastal biodiversity.